Model Pembelajaran Al-Qur’an Berbasis Neurosains dalam Meningkatkan Minat Dan Konsentrasi Anak Usia 4-5 Tahun di PAUDQ Nur Fadhilatul Qur'an Tuban - Dwi Aminatus Sa'adah; Agus Fathoni Prasetyo; Tining (Institut Agama Islam Nahdlatul Ulama Tuban, 2025)
This research aims to determine a neuroscience-based Al-Qur'an learning model in increasing the interest and concentration of children aged 4-5 years at PAUDQ Nur Fadhilatul Qur'an Tuban. The approach used is descriptive qualitative with the Kemmis and McTaggart model of classroom action research (PTK). This research consists of four cycles: planning, implementing actions, observing, and reflecting. The research subjects were 23 group B children who showed a tendency to have low interest and concentration in learning the Al-Qur'an. Data collection was carried out through observation, interviews with teachers and parents, as well as documentation of activities. Data were analyzed using the Miles and Huberman interactive analysis model, which includes data reduction, data presentation, and drawing conclusions. The research results show that the application of a neuroscience-based learning model, which integrates multisensory stimulation and positive emotions, has succeeded in increasing children's interest and concentration in learning the Koran. Children are more involved in learning that uses educational games, songs, movements and visualization, which suit the way a child's brain works. This approach has proven effective in improving learning outcomes, as well as providing a fun and meaningful learning experience, which also instills Islamic spiritual values ​​from an early age.